Loach hatching device facilitating establishment of family - MA BENHE; WANG HAIHUA; WU BIN; LI YANHUA; LUO NAN (2021)
The utility model provides a loach hatching device convenient for establishing a family, which belongs to the technical field of loach breeding and comprises a water pipe, a hatching barrel and a spun yarn net, the bottom of the hatching barrel is communicated with the water pipe, the spun yarn net is positioned at the top of the hatching barrel, a fixing block is fixedly connected with a port of the water pipe, and the fixing block is fixedly connected with a fixing rod. An inflation pipe is inserted in the position, opposite to the hatching barrel, of the bottom of the water pipe, a round block is arranged on the inner wall of the hatching barrel, a fixing column is fixedly connected to the bottom of the round block, a driving rod slidably penetrates through the surface of the hatching barrel, tooth grooves are formed in the surfaces of the fixing column and the driving rod, and the surface of the driving rod is meshed with the fixing column. And a driving device is arranged on the surface of the fixed bloc